2000
DOI: 10.1007/s11894-000-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic bone disease in IBD

Abstract: A substantial number of patients with inflammatory bowel disease (IBD) will manifest extra-intestinal complications. Metabolic bone disease and arthropathies are among the most debilitating of these. Decreased bone mineral density and increased fracture risk may occur in relation to the underlying disease itself or result from vitamin, mineral, and hormonal deficiencies; medications used to treat the underlying disease; lifestyle; and perhaps other factors. In many cases, the factors remain unidentified. Optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Bone loss has long been recognized as an extraintestinal complication of inflammatory disorders of the gut, such as Crohn's disease and ulcerative colitis (115). One recent study found that patients with these diseases have elevated levels of serum OPG, which derive from the site of inflammation and inversely correlate with severity of bone loss (116), whereas another study found that Crohn's disease patients have elevated levels of both OPG and soluble TRANCE (117).…”
Section: Autoimmunity Bone and Trance: The Birth Of Osteoimmunologymentioning
confidence: 99%
“…Bone loss has long been recognized as an extraintestinal complication of inflammatory disorders of the gut, such as Crohn's disease and ulcerative colitis (115). One recent study found that patients with these diseases have elevated levels of serum OPG, which derive from the site of inflammation and inversely correlate with severity of bone loss (116), whereas another study found that Crohn's disease patients have elevated levels of both OPG and soluble TRANCE (117).…”
Section: Autoimmunity Bone and Trance: The Birth Of Osteoimmunologymentioning
confidence: 99%
“…Metabolic bone disease and arthropathies are often the most debilitating extra-intestinal manifestations of intestinal failure [32]. Osteoporosis was detected in 67% of patients with intestinal failure [33].…”
Section: Indicationsmentioning
confidence: 99%
“…However, HPN has no deleterious effect on cortical bone and actually improves trabecular bone in patients whose intestinal disease started after the age of 21 years [33]. The etiology is multifactorial involving calcium and phosphate deficiency, aluminum toxicity, lack of periodic enteral feeding, malabsorption, inflammation, and drug-induced alterations in calcium and bone metabolism [32,34]. Bone metabolism disorders are more common than liver diseases, and one third of HPN patients regularly consumed analgesics or opiates [35].…”
Section: Indicationsmentioning
confidence: 99%